PRODUCTIVITY OF SOYBEAN DEPENDSNG OF THE PREDECESSOR, WEATHER CONDITION AND EFFICIENCY OF HERBICIDES - Зуза, В. С.; Рожков, А. О.; Гутянський, Р. А. (Scientific Progress & Innovations, 2015)
The results of four years research of the influence of predecessors, including winter wheat and spring barley and soil herbicide Harnes on productivity soybean in years with different levels of moisture providing are presented. It is installed, that soil herbicide Harnes controlled the total wet weight number of weeds after the winter wheat predecessor respectively 92 and 93 %, and after predecessor of spring barley – 91 and 83 %. We found that after winter wheat predecessor yield of soybean was formed more than after spring barley.